Penyusunan Laporan Keuangan Berdasarkan SAK EMKM Pada Droplets Workshop - Fajar Maulana Ramdhania (Indonesian Accounting Literacy Journal, 2022)
Micro, Small, and Medium Enterprises (MSMEs) have a big role in improving the Indonesian economy. Droplets Workshop is a micro-business referring to government regulation number 7 of 2021 which produces leather products such as bracelets, wallets, keychains, and other leather products. However, Droplets Workshop has not been able to compile financial statements due to a lack of knowledge and skills in preparing financial statements, even though financial statements can be used as material for evaluating performance, knowing asset conditions, business development, tax reporting, and as a condition for obtaining funding from financial institutions. Therefore, this study aims to prepare financial statements based on SAK EMKM at Droplets Workshop. The research method used is descriptive qualitative and data collection techniques which are interviews, documentation, observation, and literature study. The final result of this research is the required financial statements in SAK EMKM in the form of income statements, statements of financial position, and notes to financial statements. It is also expected to be a consideration for companies to carry out recording and bookkeeping according to standards.